Correlation of Recurrence of Pleomorphic Adenoma of Parotid Gland with Tumor Size and Resection Margin: A Retrospective Study - Dutta, Vijay Bhushan; Agarwal, Sangeet Kumar; Yeramalla, Vijay; Gupta, Arushi (Med Phoenix, 2025)
Introduction: The recurrence of pleomorphic adenoma has been attributed to various surgery related and pathology related factors. Our objective was to correlate the recurrence of the pleomorphic adenoma of parotid gland with tumor size and resection margin. Materials and methods: This study was a retrospective review of patients at a single tertiary care center who underwent operations for pleomorphic adenoma of the parotid gland between 2011 and 2021. Demographic data, details of surgical interventions, histopathological reports and recurrence rates were studied. The recurrence of pleomorphic adenoma was correlated with the size of the tumor and resection margin. Chi-square and regression analysis were used for statistical analysis. Results: A total of 157 patients were included in the study. The recurrence rate of the tumor of size up to 2 cm, 2-4cm and larger than 4cm were 0%, 1.1% and 14.3% respectively. Adequate surgical margin was achieved in 66.7%, 52.1% and 42.8% of patient with tumor up to 2cm, 2-4cm and larger than 4cm respectively. No recurrences were seen in patients with adequate surgical margin whereas 5.6% of the patients with exposed tumor had recurrence. Tumor with both inadequate resection margin and large size (4cm or larger) had recurrence rate of 33.33%. Conclusion: This study demonstrated size of pleomorphic adenoma and resection margin after parotidectomy as significant factor for recurrence. The tumor more than 4cm in diameter with inadequate resection margin had high recurrence of 33.33% which is close to enucleation. Moreover, it is difficult to obtain adequate soft tissue margin in larger tumors.